Bis(alkylidynyl)arsines. Issue 55 (22nd June 2018) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : The synthesis and characterization of the first examples of bimetallic bis(alkylidynyl)arsines are described. For the tungsten complexes, these may be prepared by a potentially generalizable route: successive treatment of [W(CBr)(CO)2 (Tp*)] with n BuLi, ACl3 (A = P, As) and a nucleophilic source of R − via the inferred intermediacy of [ClA{CW(CO)2 (Tp*)}2 ]. Abstract : The synthesis and characterization of the first examples of bimetallic bis(alkylidynyl)arsines, [RAs{CM(CO)2 (Tp*)}2 ] (M = Mo, R = Ph, Me; M = W, R = Ph, Me, n Bu; Tp* = hydrotris(3, 5-dimethylpyrazol-1-yl)borate) are described. For the tungsten complexes, these may be prepared by a potentially generalizable route: successive treatment of [W(CBr)(CO)2 (Tp*)] with n BuLi, ACl3 (A = P, As) and a nucleophilic source of R − via the inferred intermediacy of [ClA{CW(CO)2 (Tp*)}2 ].